Tindak Pidana Penganiayaan Ringan: Sebuah Perspektif - Mustafa, Winarti; Abdulajid, Syawal; Amriyanto, Amriyanto (Legal Spirit, 2024)
Restorative Justice is a new approach emphasizing dialogue and peace in crime resolution, prioritizing addressing the core issues between individuals. In cases of assault, which involve unlawful acts causing harm or injury, Restorative Justice is typically applied to minor cases. However, Police Regulation Number 8 of 2021 expands Restorative Justice to encompass both minor and severe assault cases, as implemented in North Halmahera Police Resort. This empirical research collects primary and secondary data through field studies and literature reviews, employing qualitative analysis. Findings highlight the urgency of police implementation of Restorative Justice in assault cases to achieve substantial and balanced justice. Implementation has occurred in North Halmahera Police Resort in accordance with Police Regulation Number 8 of 2021, yet faces challenges such as socialization, cultural adaptation, and coordination between victims and perpetrators. Future law enforcement policies based on Restorative Justice must adapt to existing challenges, including wider socialization and cultural adaptation. Understanding the importance of victims' and perpetrators' presence in the Restorative Justice process also requires enhancement.